The relationship between corporate social responsibility and sustainable development : Theoretical approach - DJESSAS, Mohamed (Journal of Human Sciences, 2020)
This paper aims to discuss Corporate Social Responsibility and sustainable development by analyzing the nature of the theoretical and practical relationship between the two concepts.We showed by our study that the concept of corporate social responsibility has been studied separately for a long period of time and away from sustainable development, But the growth of multinational corporations which exceeded their economic strength the strength of the economies of many countries, focus on actors in sustainable development, from the responsibility of Governments and civil society actors, to responsibility of the business sphere at the beginning of the third millennium. it has become  clear  by  now  that Sustainable development’s goals Cannot be achieved without the contribution of the business sector through social responsibility initiatives.